Proceedings of the Twenty-Seventh Annual ACM-SIAM Symposium on Discrete Algorithms 2015
DOI: 10.1137/1.9781611974331.ch112
|View full text |Cite
|
Sign up to set email alerts
|

Tight Bounds for Graph Homomorphism and Subgraph Isomorphism

Abstract: We prove that unless Exponential Time Hypothesis (ETH) fails, deciding if there is a homomorphism from graph G to graph H cannot be done in timeWe also show an exponential-time reduction from Graph Homomorphism to Subgraph Isomorphism. This rules out (subject to ETH) a possibility of |V (H)| o(|V (H)|) -time algorithm deciding if graph G is a subgraph of H. For both problems our lower bounds asymptotically match the running time of brute-force algorithms trying all possible mappings of one graph into another. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Corollary 2 in particular excludes any algorithm for testing homomorphisms into Kneser graphs with running time 2 O(n+h) . It cannot give a tight lower bound matching the result of Cygan et al [9] for general homomorphisms, because h = |V (KG a,b )| = a b is not polynomial in b. On the other hand, it exhibits the first explicit family of graphs H for which the complexity of Graph Homomorphism increases with h.…”
Section: Corollarymentioning
confidence: 82%
See 1 more Smart Citation
“…Corollary 2 in particular excludes any algorithm for testing homomorphisms into Kneser graphs with running time 2 O(n+h) . It cannot give a tight lower bound matching the result of Cygan et al [9] for general homomorphisms, because h = |V (KG a,b )| = a b is not polynomial in b. On the other hand, it exhibits the first explicit family of graphs H for which the complexity of Graph Homomorphism increases with h.…”
Section: Corollarymentioning
confidence: 82%
“…For quite a while it was open whether there is an algorithm for Graph Homomorphism running in time 2 O(n+h) . It was recently answered in the negative by Cygan et al [9]; more precisely, they proved that an algorithm with running time 2 o(n log h) would contradict the Exponential Time Hypothesis (ETH) of Impagliazzo et al [23]. However, Graph Homomorphism is a very general problem, hence researchers try to uncover a more fine-grained picture and identify families of graphs H such that the problem can be solved more efficiently whenever H ∈ H. For example, Fomin, Heggernes and Kratsch [13] showed that when H is of treewidth at most t, then Graph Homomorphism can be solved in time O ⋆ ((t + 3) n ).…”
Section: Introductionmentioning
confidence: 99%
“…By Theorem 13 it then follows that for every |D| ≥ 3 there exists B such that CSP(R D = )-B is NP-complete but not solvable in subexponential time, unless the ETH is false. The ETH-hardness for degree-bounded k-coloring is typically referred to as folklore (see, e.g., Cygan et al [22,Lemma 1]), but our results show that this property can be phrased in a purely algebraic manner.…”
Section: Complexity Of Csps In Light Of the Ethmentioning
confidence: 60%
“…The idea of using harmonious coloring for proving lower bounds of the form 2 o( 2 ) n O (1) was used by Agrawal et al [1] to prove a lower bound for Split Contraction, when parameterized by the vertex cover number , of the input graph. Also, the idea of partitioning vertices 60:3 of the input graph based on some coloring scheme was used by Cygan et al [10] to prove ETH-based lower bounds for Graph Homomorphism and Subgraph Isomorphism.…”
Section: Inputmentioning
confidence: 99%